Praktik Pemberian Nafkah Anak Hasil Pernikahan Siri di Kawahmanuk, Kabupaten Kuningan: (Suatu Tinjauan Komparatif Hukum Islam dan Hukum Positif) - Syafi'i, Alfan; Dzulkifli, Diki (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2024)
The livelihood of children resulting from Siri (unregistered) Marriages is a problem in the Kawahmanuk Village, Darma District, Kuningan Regency because they don't fully receive rights from their parents. The target of this research is to analyze the practice of providing livelihood for children resulting from Siri Marriages in Kawahmamnuk Village, Darma District, Kuningan Regency, Beside that, this research also object to analyze how children resulting from unregistered marriages are provided for according to Islamic law and positive law in Kawahmanuk Village, Darma District, Kuningan Regency as well as comparing Islamic law and positive law regarding the maintenance of children resulting from unregistered marriages in Kawahmanuk Village, Darma District, Kuningan Regency. The investigation method uses qualitative methods, the type of research is field research and the data collection technique used in this research is a structured interview technique. The results of this study are First, the practice of providing for children resulting from siri marriages in Kawahmanuk Village, Darma District, Kuningan Regency is the same as marriages in general, where the responsibility for providing for children resulting from siri marriages on the husband, although sometimes fully provided or insufficient. Second, according to Islamic law, the obligation to provide support for children resulting from an siri marriage in Kawahmanuk Village, Darma District, Kuningan Regency is the same as for marriages in general, where the responsibility for providing for children resulting from an siri marriage lies with the husband. Third, according to positive law, the obligation to provide support for children resulting from siri marriages in Kawahmanuk Village, Darma District, Kuningan Regency is different from marriages in general, where the marriage has no legal force, the husband does not have to be responsible for the child's support, and the child has no right to claim support. Fourth, a comparison of Islamic law and positive law regarding the maintenance of children resulting from siri marriages in Kawahmanuk Village, Darma District, Kuningan Regency, that according to Islamic law the obligation to provide support for children resulting from siri marriages is like in marriages in general, where the husband must be fully responsible for the child's maintenance, whereas according to positive law, this marriage does not abide by the law, and fathers do not have to be responsible for the maintenance of children resulting from siri marriages, and children cannot claim their rights.